Computer-based malay speech analysis system for speech theraphy system - Helbin Liboh, 1984-; Sheikh Hussain Shaikh Salleh, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011